2021
DOI: 10.1108/ijm-03-2021-0175
|View full text |Cite
|
Sign up to set email alerts
|

Developing human resource for the digitization of logistics operations: readiness index framework

Abstract: PurposeThe purpose of this study is to identify factors that are important for logistics organizations from the perspective of manpower readiness for digitization of logistics operations. The study also prioritizes the identified factors and also evaluates the readiness index of manpower for the digitalization of logistics processes.Design/methodology/approachThe factors for manpower readiness are identified through literature review and analysis of a case study. Three major categories of factors are identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 82 publications
(131 reference statements)
0
28
0
2
Order By: Relevance
“…The GTMA can be used with an unlimited number of quantitative and qualitative determinants simultaneously (Gupta and Singh 2020 ). Moreover, GTMA provides a visual picture of the problem not considered in the conventional MCDM method (Gupta et al 2021 ). In contrast to the other methodologies, the GMTA can depict the interaction between the problem's components and express it mathematically (Hudnurkar and Ambekar 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The GTMA can be used with an unlimited number of quantitative and qualitative determinants simultaneously (Gupta and Singh 2020 ). Moreover, GTMA provides a visual picture of the problem not considered in the conventional MCDM method (Gupta et al 2021 ). In contrast to the other methodologies, the GMTA can depict the interaction between the problem's components and express it mathematically (Hudnurkar and Ambekar 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Zekhnini et al (2020) investigated key supply chains 4.0 risks and examined the relationship between them. Also, Gupta et al (2021) determined important factors for manpower readiness for digitization of logistics operations. Moreover, authors prioritized the identified factors and created the readiness index.…”
Section: Business Andmentioning
confidence: 99%
“…For example, the Hewlett-Packard company can predict how much raw material is returning to the company. Since the implementation of Industry 4.0 is oriented toward digital and virtual technologies and centered on services, it is understood that its association with CE can improve the sustainability of supply chains for companies (Jabbour et al, 2018;Gupta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%